PENGARUH MEDIA TEKNOLOGI KAHOT DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V DI SD NEGERI 091374 NAGA SARIBU - Enzel Apriliya saragih; Irmina Pinem; Jhonas Dongoran; Ester Julinda Simarmata; Dyan Wulan Sari HS; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of Kahoot technology media on student learning outcomes in the IPAS subject for Grade V at SD Negeri 091374 Naga Saribu during the 2024/2025 academic year. The research method employed is an experimental method with a quantitative research type. To obtain the necessary data, a test instrument consisting of 25 questions was used. The research sample comprised 21 students, selected using a saturated sampling technique. To assess the students' initial abilities, a Pre-Test was conducted, yielding an average score of 42.9, which falls into the 'low' category. The Post-Test results showed an improvement from the Pre-Test, with the students' average score reaching 80.38, categorized as 'good'. It can be stated that the level of student learning success increased, as evidenced by the correlation coefficient test results, where the calculated r-value (r_hitung) was greater than or equal to the table r-value (r_tabel), with results of 0.617 ≥ 0.413. Furthermore, hypothesis testing comparing the calculated t-value (t_hitung) to the table t-value (t_tabel) yielded t_hitung = 3.419 and t_tabel = 1.720. Since t_hitung ≥ t_tabel (3.419 ≥ 1.720), the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. Through this t-test, it can be concluded that there is a significant positive influence of Kahoot Technology Media (X) on student learning outcomes (Y).